Physical design of a compact injector for synchrotron-based proton therapy - Qiao, Jian; Yan, Nan; Huang, Zike; Zhong, Yang; Wang, Jiazhou; Xie, Xiucui; Pu, Yuehu; Hu, Weigang (Frontiers in Physics, 2023)
A compact room-temperature linear injector has been purposed to accelerate an 18.0 mA proton beam to 7.0 MeV for synchrotron-based proton therapy. The total length is appropriately 5 m. It mainly consists of a 3.01 m radio frequency quadrupole (RFQ) and a 0.82 m compact interdigital H-mode drift tube linac (IH-DTL) structure. Based on a fast-bunching strategy, the RFQ, operated at 325 MHz, accelerates protons to 3.0 MeV. The phase advances have been taken into consideration, and parametric resonance has been carefully avoided by adjusting the vane parameters. After the modulation of the transverse and longitudinal phase advances and a compact external quadrupole triplet, the proton beam is injected into the subsequent IH-DTL. Based on modified Kombinierte Null Grad Strukter (KONUS) beam dynamics, it accelerates protons up to 7.0 MeV, which is composed of a re-bunching section and an accelerating section. The accelerating gradient reaches 4.88 MV/m. The overall dynamic simulation results show that the whole accelerating gradient reaches up to 1.62 MV/m with a transmission efficiency above 95%. The transverse and longitudinal normalized RMS emittances at the exit of the DTL are 0.23 π mm·mrad and 2.216 π keV/u·ns, which meet the synchrotron injection requirements. The details of the specific design of this injector are presented in this paper.